Clinical Aspects of Transporter‐Mediated Drug–Drug Interactions. Issue 6 (18th March 2019) - Gessner, Arne; König, Jörg; Fromm, Martin F.
Abstract : Drug transporters play an essential role in disposition and effects of multiple drugs. Plasma concentrations of the victim drug can be modified by drug–drug interactions occurring in enterocytes (e.g., P‐glycoprotein), hepatocytes (e.g., organic anion‐transporting polypeptide 1B1 (OATP1B1)), and/or renal proximal tubular cells (e.g., organic cation transporter 2 (OCT2)/multidrug and toxin extrusion 1 and 2‐K (MATE1/MATE2‐K)). In addition, transporter‐mediated drug–drug interactions can cause altered local tissue concentrations and possibly altered effects/toxicity (e.g., in liver and kidneys). During drug development, there is now an intensive in vitro screening of new molecular entities as transporter substrates and inhibitors, followed if necessary by drug–drug interaction studies in healthy volunteers. Nevertheless, there are still unresolved issues, which will also be discussed in this review article (e.g., the clinical significance of transporter‐mediated drug–drug interactions of particular relevance to the elderly who are prescribed multiple drugs, with additional impaired liver or kidney function, and the extent to which medication safety in real life could be improved by a reduction of those interactions).